2017
DOI: 10.1016/j.jrras.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial efficacy of anise wastes against some multidrug resistant bacterial isolates

Abstract: Antibiotic resistance in bacteria is becoming a serious problem, especially after the emergence of multidrug-resistant strains. To overcome this problem, new and effective antibacterials or resistance modulators are highly needed and plant kingdom represents a valuable source of these compounds. In this study we investigated the antibacterial and resistance modulatory activity of Aniseeds waste Residue Extract (ASWRE) and Star Anise Waste Residue Extract (SAWRE) (post-distillation) against 100 isolates belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…The antibacterial activity of star anise extracts has previously been evaluated for A. baumannii ; however, even if the antibacterial activities of the star anise EO had been evaluated before, no previous reports on the activity of star anise EO on A. baumannii strains were found in the literature. Both the MIC and MBC values were determined (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of star anise extracts has previously been evaluated for A. baumannii ; however, even if the antibacterial activities of the star anise EO had been evaluated before, no previous reports on the activity of star anise EO on A. baumannii strains were found in the literature. Both the MIC and MBC values were determined (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…f.) has been widely used both as an ingredient in the traditional five‐spice powder of Chinese cooking, as a flavouring agent, and as a medicine for over 3000 years . The bioactivities of star anise extracts have already been reported, namely quorum sensing and the inhibition of biofilm formation, which are properties used against some foodborne bacteria, presenting also both antimicrobial and antioxidant activities . Although star anise essential oil (EO) has been subjected to an evaluation of its biological activities and chemical composition, an exhaustive study of the bioactivities of star anise EO, with a particular focus on A. baumannii , has not been performed previously.…”
Section: Introductionmentioning
confidence: 99%
“…China has important potential to produce aromatic and medical plants and herbs due to its various biological diversity and different climatic conditions (Chen et al, 2013;Ogbaji et al, 2013;Shahrajabian et al, 2017;Yong et al, 2017). Aromatic plants such as anise seed have a long traditional use in both folk and conventional medicine and of course in the pharmaceutical industry (Abouzid and Mohamed, 2011;Ibrahim et al, 2017). Anise (Pimpinella anisum) is a herbaceous annual plant, native to Mediterranean region and primarliy grown for both fruits and seeds (Zand et al, 2013).…”
Section: Anise 31 Occurrence and Cultivationmentioning
confidence: 99%
“…Kreydiyyeh et al (2003) found that extracts of the aniseeds are used as medicine for their diuretic and laxative effect, expectorant and anti-spasmodic action, and their ability to ease gastric pain and flatulence. Ibrahim et al (2017) reported that waste residues of anise and star anise are promising new sources of phenolic antimicrobial compounds which offer new commercial opportuities to pharmaceutical industry. They have suggested that combination of anise waste extracts with some antibiotics leads to new choice for treatment of infectious diseases and waste extracts may act as activity modifying agent for antibiotics.…”
Section: Anise Nutritional Composition and Chemical Constituentsmentioning
confidence: 99%
“…The seeds have been commonly used for folk medicine, pharmacy, food industry and even as a spice [3]. There are many reports about antibacterial [4], anti-oxidative [5], antitoxicity [6] and also anticancer [7] effects of essential oils in aniseed. On the other hand, there is still some concern related to the safety and efficiency.…”
Section: Introductionmentioning
confidence: 99%